2000
DOI: 10.1128/iai.68.8.4699-4705.2000
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Platelets and Platelet Microbicidal Protein Susceptibility on the Fate of Staphylococcus aureus in an In Vitro Model of Infective Endocarditis

Abstract: Several lines of evidence indicate that platelets protect against endovascular infections such as infective endocarditis (IE). It is highly likely that a principal mechanism of this platelet host defense role is the release of platelet microbicidal proteins (PMPs) in response to agonists generated at sites of endovascular infection. We studied the ability of platelets to limit the colonization and proliferation of Staphylococcus aureus in an in vitro model of IE. Three isogenic S. aureus strains, differing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…These peptides limit the progression of the disease. Staphylococcus aureus strains resistant to tPMP may grow faster in the presence oftPMP than susceptible strains, and the vegetation size rate and progression rate was higher in rabbits infected by tPMP resistant strains (14)(15)(16). tPMP susceptibility of the infective organism may affect the entire course of the disease regarding both local and systemic lesions.…”
Section: Procoagulant Activity Following Endothelial Cell Injurymentioning
confidence: 99%
“…These peptides limit the progression of the disease. Staphylococcus aureus strains resistant to tPMP may grow faster in the presence oftPMP than susceptible strains, and the vegetation size rate and progression rate was higher in rabbits infected by tPMP resistant strains (14)(15)(16). tPMP susceptibility of the infective organism may affect the entire course of the disease regarding both local and systemic lesions.…”
Section: Procoagulant Activity Following Endothelial Cell Injurymentioning
confidence: 99%
“…ISP479R exhibits reduced killing by low levels of tPMP-1 in vitro (e.g., Ն90% survival of a 10 3 CFU/ml inoculum following 2 h of exposure to 2 g of tPMP-1 at 37°C), compared with that of tPMP-1-susceptible ISP479C (Յ25% survival under identical test conditions). These strains have been described in detail previously (24,26,36).…”
Section: Organismsmentioning
confidence: 99%
“…However, given our current and prior in vitro and in vivo data, 10,[12][13][14][15] it appears reasonable to hypothesize that the local secretion of tPMPs from activated platelets at sites of vegetation development may limit proliferation of tPMP-susceptible strains. This effect would likely mitigate hematogenous embolic seeding of target organs (eg, kidneys) and reduce the extent of bacteremia, key factors in ongoing microbial seeding of vegetations.…”
Section: Kupferwasser Et Al Role Of Platelet Microbicidal Proteins Inmentioning
confidence: 99%
“…8 A compelling body of recent evidence has demonstrated that the host defense function of these peptides is particularly relevant to endovascular infections caused by S aureus. 6,[12][13][14][15]27 For example, among clinical bloodstream S aureus isolates, tPMP-susceptible strains were infrequently associated with human IE compared with tPMP-resistant strains. 28 In addition, bacteremic S aureus strains from patients with IE, resulting from an infected intravascular catheter, tended to be significantly more tPMP-resistant than strains arising from a noncatheter source.…”
Section: Kupferwasser Et Al Role Of Platelet Microbicidal Proteins Inmentioning
confidence: 99%
See 1 more Smart Citation